2014
DOI: 10.1177/0300060514533525
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin and obestatin plasma levels and ghrelin/obestatin prepropeptide gene polymorphisms in small for gestational age infants

Abstract: Ghrelin/obestatin prepropeptide polymorphisms were not found to be associated with SGA status in neonates; however, ghrelin and obestatin levels may be involved in growth and development. Further studies are required to understand the relationship between ghrelin, obestatin and prenatal development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…As expected, in our study the GHRL rs696217 T allele showed a statistically significant association with waist circumference and hip circumference level in all subjects. The GHRL Arg51Gln [rs34911341 (C>T)] was associated with hypertension in Caucasian subjects [35], on the other hand, the 51Gln marker has been found to have a protective factor against the development of T2DM [24,36]. The Arg51 residue is a site for proteolytic cleavage to synthesis ghrelin, and its substitution to the 51Gln variant leads to lower ghrelin plasma levels, resulting in less abundant synthesizing of the preproghrelin peptide [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, in our study the GHRL rs696217 T allele showed a statistically significant association with waist circumference and hip circumference level in all subjects. The GHRL Arg51Gln [rs34911341 (C>T)] was associated with hypertension in Caucasian subjects [35], on the other hand, the 51Gln marker has been found to have a protective factor against the development of T2DM [24,36]. The Arg51 residue is a site for proteolytic cleavage to synthesis ghrelin, and its substitution to the 51Gln variant leads to lower ghrelin plasma levels, resulting in less abundant synthesizing of the preproghrelin peptide [37].…”
Section: Discussionmentioning
confidence: 99%
“…The GHRL Leu72Met variant and obesity-related phenotype and metabolic diseases vary according to different populations. Surprisingly, there is no study to show any association of the GHRL c.152C>T (p.Arg51 Gln) (rs34911341) variant and being obese in the literature [ 24 ]. Detection of gene variants and modifiers that might regulate the gene expression are crucial.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with those of previous studies that have shown an OB-induced reduction in MDA levels in different experimental models. 15,19 SODs are enzymes that catalyze the dismutation of superoxide into oxygen and hydrogen peroxide. High SOD levels in the immature and newborn's intestines are known to exert a protective effect against intestinal ischemia and reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Studies associated with OB in newborns are related only to plasma OB levels. 18,19 In these studies, the OB levels in newborns with different birth weights according to gestational age were investigated. It was reported that small for gestational age newborns have higher plasma OB levels than large for gestational age newborns, and it has been suggested that OB levels may be involved in growth and development in newborns.…”
mentioning
confidence: 99%
“…However, some studies have different findings. That is, no difference was observed in the serum ghrelin levels between full-term and preterm infants and between AGA and large for gestational age (LGA) infants ( 19 , 41 , 42 ). Moreover, SGA neonates have lower cord blood ghrelin levels ( 43 ).…”
Section: Role Of Ghrelin In Fetal Developmentmentioning
confidence: 99%